غريب القرآن الكريم في تفسير التحرير والتنوير من سورة الأحقاف إلى سورة الذاريات - تي, مفيدة (University of eloued جامعة الوادي, 2016)
تناول البحث في هذه المذكرة دراسة علم غريب القرآن الكريم عند الإمام محمد الطاهر بن عاشور من خلال تفسيره التحرير والتنوير، ولذا فهذا البحث يتعرض لذكر لمحة موجزة عن الإمام ابن عاشور مع أبرز محطات حياته، كذلك تتضمن هذه الدراسة التعريف بتفسيره الشهير. ويتناول هذا البحث أيضًا التعريف بعلم غريب القرآن ومعرفة تطوره ونشأته وأهم مؤلفاته ومناهج المؤلفين في التأليف فيه، كما يركّز البحث على هذا العلم في تفسير ابن عاشور وذلك بمعرفة منهجه في عرض اللفظة الغريبة وكيفية الاستدلال عليها، ومصادره في ذلك، إضافة والقسم الثاني من هذه المذكرة فهو للدراسة التطبيقية وذلك من خلال استقراء الجزء المدروس- من س ورة الأحقاف- إلى سورة الذاريات- واستخراج الألفاظ الغريبة ودراستها ومقارنتها بأقوال أهل العلم من اللغويين وأصحاب الغريب والمفسرينثم في الختام خاتمة تحمل أهم النتائج وأهم التوصيات المقترحة. The research in this letter is a study of a nation flags « Imam Mohamed Tahar Ben Achour » and the subject of strange Koran with him through his interpretation liberation and enlightenment, and so this research is exposed to mention a brief overview of the life of Imam with leading his stations, this study also includes definition of the famous interpretation. This research deals with the definition also with the knowledge of the Koran and the strange .knowledge of its origins and evolution, and the most important files and authors curricula This research on this science in the interprétation of Ben Achour focused by knowing his approach in the presentation of exotic language and how to infer the sources and in that, in addition to the properties that distinguish them this explanation to explain the strange vocalisations. his research on this science in the interpretation of Ben Achour focused by knowing his approach in the presentation of exotic language and how to infer the sources and in that, in addition to the properties that distinguish them this explanation to explain the strange vocalizations. The second chapter devoted to the study and applied it in part through extrapolation studied - from al-ahqaf - to Surat Almariaat- and extraction of exotic words and study and compare with statements of the scholars of linguists and the owners of the strange and commentators. In conclusion a summary take the most important
ماستر علوم القران
Keywords: غريب,القرآن الكريم,تفسير التحرير,التنوير,سورة الأحقاف,سورة الذاريات; Strange, the Noble Qur’an, the interpretation of liberation, the enlightenment, Surat Al-Ahqaf, Surat Al-Dhariyat